(untitled) (Journal of Enam Medical College, 2015)
Background: Friedewalds formula (FF) is used worldwide to calculate low-density lipoprotein cholesterol (LDL-chol). But it has several shortcomings: overestimation at lower triglyceride (TG) concentrations and underestimation at higher concentrations. In FF, TG to very low-density lipoprotein cholesterol (VLDL-chol) ratio (TG/VLDL-chol) is considered as constant, but practically it is not a fixed value. Recently, by analyzing lipid profiles in a large population, continuously adjustable values of TG/VLDL-chol were used to derive a novel method (NM) for the calculation of LDL-chol. Objective: The aim of this study was to evaluate the performance of the novel method compared with direct measurement and regression equation (RE) developed for Bangladeshi population. Materials and Methods: In this cross-sectional comparative study we used lipid profiles of 955 adult Bangladeshi subjects. Total cholesterol (TC), TG, HDL-chol and LDL-chol were measured by direct methods using automation. LDL-chol was also calculated by NM and RE. LDL-chol calculated by NM and RE were compared with measured LDL-chol by twotailed paired t test, Pearsons correlation test, bias against measured LDL-chol by Bland-Altman test, accuracy within ±5% and ±12% of measured LDL-chol and by inter-rater agreements with measured LDL-chol at different cut-off values. Results: The mean values of LDL-chol were 110.7 ± 32.0 mg/dL for direct measurement, 111.9 ± 34.8 mg/dL for NM and 113.2 ± 31.7 mg/dL for RE. Mean values of calculated LDL-chol by both NM and RE differed from that of measured LDL-chol (p<0.01 for NM and p<0.0001 for RE). The correlation coefficients of calculated LDL-chol values with measured LDL-chol were 0.944 (p<0.0001) for NM and 0.945 (p<0.0001) for RE. Bland- Altman plots showed good agreement between calculated and measured LDL-chol. Accuracy within ±5% of measured LDL-chol was 49% for NM, 46% for RE and within ±12% of measured LDL-chol was 79% for both NM and RE. Inter-rater agreements (?) between calculated and measured LDL-chol at LDL-chol <100 mg/dL, 100130 mg/dL and >130 mg/dL were 0.816 vs 0.815, 0.637 vs 0.649 and 0.791 vs 0.791 for NM and RE respectively. Conclusion: This study reveals that NM and RE developed for Bangladeshi population have similar performance and can be used for the calculation of LDL-chol. DOI: http://dx.doi.org/10.3329/jemc.v5i1.21491 J Enam Med Col 2015; 5(1): 10-14